THE IMPACT OF THE STRATEGIC LENS ON ENTREPRENEURSHIP (World Bulletin of Social Sciences, 2022)
This study aims to analyze the impact of the strategic lens on the entrepreneurial orientation of organizations on a sample of managers in private commercial banks in the city of Baghdad. The importance of the study lies in the scarcity of research that dealt with strategic lenses and their role in the entrepreneurial trend in banks. Where this study dealt with the problem of the complexity of the internal and external environments of the organizations that contributed to creating problems and obstacles in the implementation of the strategy, with the lack of understanding or understanding of this issue by managers in private banks (study community). The field study tool was the questionnaire to collect information by (156) individual, which represented the number of retrieved questionnaires out of (160) questionnaires distributed to the managers working in the research sample banks, as the results of the study confirmed the existence of an impact of the strategic lens on the pioneering orientation of the banks investigated. This indicates that the approach of the strategic lens has a fundamental role in achieving the entrepreneurial orientation in the surveyed banks, and the study recommended several recommendations, the most important of which is that the managers of organizations should be motivated by change and try to look at the strategy through a set of lenses to accurately assess situations, and that organizations should Those who want to be successful in entrepreneurship should have an entrepreneurial orientation.